Comparison of 2-Hydroxyglutarate Detection With sLASER and MEGA-sLASER at 7T - Shams, Zahra; van der Kemp, Wybe J. M.; Emir, Uzay; Dankbaar, Jan Willem; Snijders, Tom J.; de Vos, Filip Y. F.; Klomp, Dennis W. J.; Wijnen, Jannie P.; Wiegers, Evita C. (Frontiers in Neurology, 2021)
The onco-metabolite 2-hydroxyglutarate (2HG), a biomarker of IDH-mutant gliomas, can be detected with 1H MR spectroscopy (1H-MRS). Recent studies showed measurements of 2HG at 7T with substantial gain in signal to noise ratio (SNR) and spectral resolution, offering higher specificity and sensitivity for 2HG detection. In this study, we assessed the sensitivity of semi-localized by adiabatic selective refocusing (sLASER) and J-difference MEsher-GArwood-semi-LASER (MEGA-sLASER) for 2HG detection at 7T. We performed spectral editing at long TE using a TE-optimized sLASER sequence (110ms) and J-difference spectroscopy using MEGA-sLASER (TE=74ms) in phantoms with different 2HG concentrations to assess the sensitivity of 2HG detection. The robustness of the methods against B0 inhomogeneity was investigated. Moreover, the performance of these two techniques was evaluated in four patients with IDH1-mutated glioma. In contrary to MEGA-sLASER, sLASER was able to detect 2HG concentration as low as 0.5 mM. In case of a composite phantom containing 2HG with overlapping metabolites, MEGA-sLASER provided a clean 2HG signal with higher fitting reliability (lower %CRLB). The results demonstrate that sLASER is more robust against field inhomogeneities and experimental or motion-related artifacts which promotes to adopt sLASER in clinical implementations.